Hip Joint Intercartilage Space, Range of Motion, and Lateral Differences in Elite and Subelite Ice Hockey Players: A Case-Control Trial - Mala, Jitka; Hybner, Tomas; Stastny, Petr (Orthopaedic journal of sports medicine, 2025)
BACKGROUND: Ice hockey players experience groin pain and imbalances in the muscles of the hip joint, possibly because of the condition of the intercartilage space (ICS). PURPOSE: To describe the lateral differences in size of the articular ICS, range of motion, and adductor/abductor muscle strength between elite and subelite ice hockey players and a control group of participants who did not play ice hockey. STUDY DESIGN: Cross-sectional study; Level of evidence, 3. METHODS: 33 elite hockey players, 26 subelite hockey players, and 30 non-ice hockey player controls were compared in terms of ICS thickness, isometric hip abductor muscle strength, hip range of motion, functional test results, and pain score. Two-way analysis of variance was used to identify differences in laterality and performance levels. RESULTS: The ICS of the hip joint was smaller (P < .001) in both groups of ice hockey players than in the control group (0.97 ± 0.11 mm) and smaller (P = .005) on the backhand side (elite 0.66 ± 0.24 mm; subelite 0.65 ± 0.15 mm) than on the forehand side (elite 0.78 ± 0.18 mm; subelite 0.74 ± 0.24 mm) in both groups of hockey players. Compared with the control (41.6°± 4°) and subelite groups, the elite group had less (P < .001) hip external rotation (elite 30.4°± 6.1°; subelite 35°± 6.5°) and internal rotation (elite 31.5°± 5.1°; subelite 35.1°± 6.5°), with no differences in laterality (P > .05). Both hockey groups had positive hip pain provocation tests and greater (P < .001) hip adduction (elite 457 ± 85 N; subelite 450 ± 82 N) and abduction (elite 429 ± 60 N; subelite 422 ± 63 N) muscle strength than the controls (adduction 347 ± 70 N; abduction 346 ± 75 N). Elite players had a greater (P = .008) adductor strength ratio on the backhand side (1.16 ± 19) than the control group (1.02 ± 0.15). CONCLUSION: Ice hockey players had a smaller ICS of the hip joint, particularly on the backhand side. These structural changes were accompanied by reduced range of motion in the hip joint, increased pain, and asymmetries in muscle strength. Hip range of motion and symmetry of adductor/abductor muscle strength should be considered when diagnosing ice hockey players. ICS assessment via sonography might become a useful tool for the evaluation of structural changes in the hip. Research on ice hockey-related injuries should focus more on the structural and functional condition of the backhand side of the hip.
Keywords: kinesiology; injury prevention; adductor strength; laterality; abductor strength